Impacts of nacl on growth and nutrients content in pineapple varieties under in vitro culture / Nur Suraya Abdullah - Abdullah, Nur Suraya (2010)
The study was conducted with the aim to evaluate the effect of sodium chloride (NaCI) on growth and nutrients content of pineapple (Ananas comosus (L.) Merrill) varieties. Explants of pineapple plantlets were cultured on MS medium treated with either 0 (control), 34, 68, 103, 137, 171, 205 or 240 mM NaCI. Four weeks after culturing, the fresh weight (FW), dry weight (DW) and number of leaves (LN) were determined. The solution for determination of nutrients content were prepared according to dry ashing method and absorbances were detected by using ICP-OES to quantify the amount of nutrients present in leaves sample. The results show that the growth of pineapple under tissue culture condition was not inhibited by salt concentration below 103 mM NaCI. Salt concentrations at 205-240 mM reduced plantlets growth significantly, but did not completely inhibit it. The results of this study indicated that the increasing of NaCI concentration in culture medium lead to the reduction of ion potassium (K+) in all pineapple varieties.